Grants of Agricultural Land for Concession Rehabilitation Under Executive Decree 21-432 of 04-11-2021 - Daha, Ahmed; Kliouat, Said (Journal of Legal Studies and Researches, 2023)
The study aims to clarify the procedures for granting agricultural land for concession rehabilitation in accordance with the provisions of Executive Decree 21-432 of 04-11-2021, with a view to enhancing the productive capacity of the agricultural sector and contributing to improving the country's food security.